Structure, Dynamics, and Phase Behavior of DOPC/DSPC Mixture Membrane Systems: Molecular Dynamics Simulation Studies. (30th June 2016) - Kim, Seonghan; Chang, Rakwoo
Abstract : Full atomistic molecular dynamics simulations have been performed for model mixture bilayer membrane systems consisting of 1, 2‐dioleoyl‐sn‐glycero‐3‐phosphocholine (DOPC) and 1, 2‐distearoyl‐sn‐glycero‐3‐phosphocholine (DSPC) phospholipids to understand the effects of two essential parameters such as lipid composition and temperature on the structural, dynamical, and phase behavior of mixture membrane systems. Although pure DSPC membranes are in the gel‐like (Lβ ′ or Pβ ′) phase at 323 K, raising the temperature by only 10 K or replacing 20% of DSPC lipids by DOPC lipids can change the gel‐like phase into the completely liquid‐crystalline phase (Lα ). This phase change is accompanied by dramatic change in both structural properties such as area per lipid, membrane thickness, deuterium order parameter, and tail angle distribution, and dynamics properties such as mobility map. We also observe that the full width at half‐maximum (FWHM) data of tail angle distribution as well as area per lipid (or membrane thickness) can be used as order parameters for the membrane phase transition. Abstract :